PERLINDUNGAN HUKUM TERHADAP KONSUMEN ATAS PENGGUNAAN BAHAN FORMALIN PADA MAKANAN DALAM PERSPEKTIF HUKUM ISLAM - Gibtiah, Gibtiah (Universitas Islam Negeri Raden Fatah Palembang, 2019)
In food production, many producers use food technology that makes food quickly damaged, becomes durable and stays good, by adding preservatives. so that the food can remain fresh, smell and taste unchanged, not quickly damaged or rot due to exposure to bacteria / fungi, however, many manufacturers cheat by adding preservatives that are harmful to the body, and can rob human lives, such as formalin, substances Formalin is a chemical that is used for external purposes, which if consumed will cause many negative effects on the body. The use of formaldehyde is prohibited in the use of additives in food. and can be held accountable for penalties in the form of administrative sanctions and penalties. So how is the legal protection of consumers using formalin hazardous substances according to the Consumer Protection Act? And what is the view of Islamic law on the practice of using formaldehyde in food? and what is the role of relevant institutions to protect consumers from formalin-related additives in Palembang City? Legal protection for consumers of formalin substances in the form of regulations and laws, among others: business actors are held accountable for losses suffered by consumers (Article 15 of the Consumer Protection Act Number 8 of 1999. Whereas in Islamic law regarding food containing formalin ingredients) , categorized as illegitimate to be eaten because it has been mixed between the halal and the haram.Based on the Fatwa of the Indonesian Ulema Council Number: 43 of 2012 concerning Formalin Abuse and other Hazardous Substances, formalin food is prohibited because it brings harm, ie if swallowed it can irritate the stomach, nausea, vomiting, and can lead to death, while those that are related to consumer protection are: a). Drug and Food Control Agency (BPOM); b). Institute for Self-Help Consumer Protection (LPKSM); c). National Consumer Protection Agency (BPKN) and d).Indonesian Consumers Foundation (YLKI). Keywords: Formalin, Undang-Undang Perlindungan Konsumen, halal food.